Electrophysiological characterisation of atrial volume receptors using ex vivo models of isolated rat cardiac atria. Issue 12 (6th November 2020) - Campbell, Thomas; Shenton, Fiona Cameron; Lucking, Eric; Pyner, Susan; Jones, James Francis Xavier
Abstract : New Findings: What is the central question of this study? What ex vivo preparation of the rat's cavoatrial junction is efficient for characterising atrial mechanoreceptors? What is the main finding and its importance? Of four different ex vivo preparations, static pressure, flow, open and euthermic, the optimal preparation was the euthermic one and involved direct recording from the right cardiac vagal branch with a Langendorff style perfusion at 37°C. Type A receptors were most common, and appeared insensitive to stretch and sensitive to atrial contraction. Type B and intermediate receptors were not isolated at 20°C but were observed closer to 37°C. The findings may suggest that type A and B receptors utilise different molecular transduction mechanisms. Abstract: Atrial volume receptors are a family of afferent neurons whose mechanically sensitive endings terminate in the atria, particularly at the cavoatrial junctions. These mechanosensors form the afferent limb of an atrial volume receptor reflex that regulates plasma volume. The prevailing functional classification of atrial receptors arose as a result of in vivo recordings in the cat and dog and were classified as type A, B or intermediate according to the timing of peak discharge during the cardiac cycle. In contrast, there have been far fewer studies of the common small laboratory mammals such as the rat. Using several ex vivo rat cavoatrial preparations, a total of 30 successful single cavoatrial mechanosensory recordings were obtained. These experiments show that the rat possesses type A, B and intermediate atrial mechanoreceptors as described for larger mammals. Recording these cavoatrial receptors proved challenging from the main vagus, but direct recording from the cardiac vagal branch greatly increased the yield of mechanically sensitive single units. In contrast to type A units, type B atrial mechanoreceptor activity was never observed at room temperature but required elevation of temperature to a more physiological range in order to be detected. The adequate stimulus for these receptors remains unclear; however, type A atrial receptors appear insensitive to direct atrial stretch when applied using a programmable positioner. The findings may suggest that type A and type B atrial receptors utilise different molecular transduction mechanisms. Abstract :